Update on fluid biomarkers for neurodegenerative diseases - Zetterberg, Henrik (Henry Stewart Talks, 2022)
Fluid biomarker candidates for neurodegenerative disease, Amyloid pathology, CSF and plasma/serum NfL, CSF Aβ42 in Alzheimer’s disease and neuroinflammatory diseases, Tau pathology in Alzheimer’s disease, Neurodegeneration, CSF and plasma NfL as biomarkers for disease progression, Drug treatment and NfL levels